Pengembangan Bahasa Anak dengan Gangguan Pendengaran melalui Pendekatan Visual-Auditori - Koimah Muslimah; Syamsiah Depalina (BLAZE : Jurnal Bahasa dan Sastra dalam Pendidikan Linguistik dan Pengembangan, 2025)
This study aims to examine the effectiveness of the visual-auditory approach in developing the language skills of early childhood children with hearing impairments at PAUD Panyabungan. Hearing impairment often hinders both receptive and expressive language acquisition. The visual-auditory approach was chosen because it combines visual stimulation (images, lip movements, gestures) and auditory stimulation (sounds, music, pronunciation), providing a complementary strategy to support children's language abilities. The research used classroom action research with two cycles, involving 5 children with hearing impairments as the subjects. The results showed a significant improvement in children’s language abilities, including understanding simple instructions, recognizing vocabulary, and expressing ideas through simple sentences. Children responded positively to visual media and pronunciation exercises combined with movement. This study concludes that the visual-auditory approach is effective in fostering language development in children with hearing impairments at the early childhood education level.